Impact of the Types and Relative Quantities of IGHV Gene Mutations in Predicting Prognosis of Patients With Chronic Lymphocytic Leukemia - Kaufman, Matthew; Yan, Xiao-Jie; Li, Wentian; Ghia, Emanuela M.; Langerak, Anton W.; Rassenti, Laura Z.; Belessi, Chrysoula; Kay, Neil E.; Davi, Frederic; Byrd, John C.; Pospisilova, Sarka; Brown, Jennifer R.; et al. (Frontiers in Oncology, 2022)
CLL patients with mutated IGHV genes (M-CLL) have better outcomes than patients with unmutated IGHVs (U-CLL). Since U-CLL patients usually express membrane immunoglobulins (IGs) that are more autoreactive and more effectively transduce signals to leukemic B cells, B-cell receptor (BCR) signaling is likely at the heart of the worse outcomes of CLL cases without/few IGHV mutations. A corollary of this conclusion is that M-CLL patients follow less aggressive clinical courses because somatic IGHV mutations have altered BCR structures and no longer bind stimulatory (auto)antigens and so cannot deliver trophic signals to leukemic B cells. However, the latter assumption has not been tested. We addressed the latter by measuring the relative numbers of replacement mutations that lead to non-conservative amino acid changes (Rnc) and the combined numbers of replacement mutations resulting in conservative amino acid changes (Rc) plus silent mutations (S) that cannot change amino acids, “(S+Rc) to Rnc IGHV mutation ratio”. When comparing time-to-first-treatment (TTFT) of patients with (S+Rc)/Rnc ≤ 1 and >1, each group had similar TTFTs, even after matching the groups for equal numbers of samples and identical numbers of mutations per sample. Thus, BCR structural change might not be the main reason for better outcomes for M-CLL patients. Rather, since the total number of IGHV mutations in a CLL patient associates with longer TTFT, better clinical courses might result from the biologic state achieved by a B cell after undergoing many germinal center reactions. Analyses of larger patient cohorts will be needed to definitively answer this question.